Welcoming The Provincial Sports Week: Self-Management Training to Improve Physical Activity and Fitness of Tasikmalaya Futsal Athletes During The Covid-19 Pandemic - Lutfi Nur; Esya Anesty Mashudi; Les Pingon; Arief Budiman (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Just like other sectors in society, The COVID-19 pandemic also affects the sports sector, especially athletes. Toward the provincial sports week of West Java, futsal athletes from various sub-districts in Tasikmalaya City carried out joint training activities. However, several problems were detected in these joint training activities, including short duration of training each day due to PPKM (public activity restrictions) regulations, decreased motivation of athletes for post-quarantine training and social restrictions, decreased frequency of physical activity and fitness levels, and the lack of athletes' performance during the training. Responding to these problems, the National Sports Committee of Indonesia (KONI) of Tasikmalaya City had a courtesy visit to UPI Tasikmalaya Campus. Both parties agreed to organize training activities with a practical and motivational approach, through the application of self-management techniques rooted in behavioral therapy. This training activity aims at helping athletes to manage physical activity schedules to improve their fitness and performance. The training activities were carried out for 48 hours online and offline. A series of training activities could be carried out properly and resulted in outputs in the form of (1) a paper presented in a scientific forum; (2) Publication of a scientific article in community service journals with ISSN; (3) publication in mass media; (4) other science and technology outputs; and (5) Innovation Products in the form of guidelines for the implementation of training activities.